The use of sodium salt deposits in medical and medically associated industries in Ancient Egypt - Sapsford, M. (Department of Applied Science, Security and Resilience, 2009)
The utilisation of minerals in Ancient Egyptian medicine from procurement through to use is examined here in a case study investigating the role of sodium salts. The sodium salts, salt and natron are two of the three most commonly used minerals in the Egyptian pharmacopeia. The results of the project are important to medical historians and archaeomineralogists alike in that they formulate a systematic understanding of the way in which minerals were used in medical and medically associated industries. Key sources of salt and natron were examined and the Wadi Natrun was identified as the probable main site of natrun exploitation. A comprehensive study conducted of this area involved examining sources of a historical geographical nature and analysis of mineralogical samples gathered from fieldwork in the Wadi Natrun. From the source of exploitation, natron and salt were sold to the Egyptians to be used in a number of everyday industries as well as for their use in medical and medically associated industries. Salt and natron were found to be used for their astringent and cleansing qualities, and are still being used in traditional medical formulations. Prescription replication showed that these substances worked effectively. Additional research into medically associated industries showed commonality between sodium salts use between all three industries investigated. The results of this research shows that a comprehensive study of the use of minerals in medicine could be established. Primary sites of exploitation of both salt and natron were identified, and minerals from theses sites were categorised and identified. The results showed that the chemical nature of these deposits had changed in the last 2000 years. The results also demonstrate reasons why the language surrounding the term natron needed to be revised. These results have implications for both archaeology and the history of medicine.
Keywords: Egypt - Civilization; Sodium salts; Ancient Egyptian medicine; Ancient medicine